Consistency tests of comparative advantage measures: an empirical evidence from the Malaysian and selected Asian shrimp products - Ng, Xin Khai; Ismail, Mohd Mansor; Ahmad Sidique, Shaufique Fahmi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The aim of this study is to examine the consistency between the Balassa index and Vollrath indices in measuring comparative advantages of the Malaysian shrimp products with other major shrimp exporting nations as comparator. The study uses Balassa index and Vollrath indices to measure comparative advantages of the Malaysian shrimp products. The indices then are compared by consistency tests. Malaysia was generally not competitive in shrimp trade; however, revealed comparative advantage (RCA) and relative export advantage (RXA) indices show some extent of competitiveness on non-frozen shrimp product. Thailand had a remarkable competitiveness in shrimp trade as compared to other major exporting countries. Although we found that double-counting problem in the Balassa index is insignificant in measuring export performance of the Malaysian shrimp sector, import could be an important variable in accessing its trade competitiveness. Marginal import of a sector may lead to relative trade advantage (RTA) index consistent with RCA and RXA indices. Considering exports and imports of a particular commodity in measuring competitiveness is more consistent with the real world phenomenon of two-way trade. Selecting measurement of comparative advantage should rigorously base on trade behaviour of a sector as well as theoretical constructs. The competitiveness of the Malaysian shrimp products remains unclear due to the lack of contemporary analyses backed by formal testing procedures. The results and policy implications of this study provide stakeholders insights into comparative advantage as well as trade position of the products. Better measurement for revealed comparative advantage, particularly for shrimp products, is discussed in this paper.